2017
DOI: 10.1186/s13059-016-1140-8
|View full text |Cite|
|
Sign up to set email alerts
|

Dual RNA-seq reveals viral infections in asthmatic children without respiratory illness which are associated with changes in the airway transcriptome

Abstract: BackgroundRespiratory illness caused by viral infection is associated with the development and exacerbation of childhood asthma. Little is known about the effects of respiratory viral infections in the absence of illness. Using quantitative PCR (qPCR) for common respiratory viruses and for two genes known to be highly upregulated in viral infections (CCL8/CXCL11), we screened 92 asthmatic and 69 healthy children without illness for respiratory virus infections.ResultsWe found 21 viral qPCR-positive and 2 suspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 68 publications
4
59
3
Order By: Relevance
“…Wesolowska‐Andersen et al recently detected a respiratory virus in 13% of symptom‐free asthmatic children and healthy controls using quantitative PCR, which is considerably lower than the percentage we found in symptom‐free children. This difference is likely explained by the age difference between the studies: 1‐to‐4‐year‐olds in our study, compared to 10‐to‐21‐year‐olds in the previous study.…”
Section: Discussioncontrasting
confidence: 86%
“…Wesolowska‐Andersen et al recently detected a respiratory virus in 13% of symptom‐free asthmatic children and healthy controls using quantitative PCR, which is considerably lower than the percentage we found in symptom‐free children. This difference is likely explained by the age difference between the studies: 1‐to‐4‐year‐olds in our study, compared to 10‐to‐21‐year‐olds in the previous study.…”
Section: Discussioncontrasting
confidence: 86%
“…Biomarkernegative, virus-positive samples could represent infections that are not currently part of an active disease process. Recent studies show that while host antiviral responses can be detected in the respiratory tract of asymptomatic virus-infected subjects, the magnitude of transcriptional response (and possibly the presence of a response at the protein level) is greater in symptomatic than asymptomatic subjects [13,[33][34][35]. Consistently, analysis of rhinovirus-positive samples in Study 2 showed a clear correlation between low [CXCL11] and low viral load (Supplementary Figure S4).…”
Section: Discussionsupporting
confidence: 60%
“…LiCl is known to regulate C/EBP-α expression [76], and thereby links the action of eIF2B to the lack of C/EBP-α in asthma patients described earlier [75]. Signalling via eIF2 was indicated to be affected by viral infection of the respiratory duct in children based on transcriptomic assessment [77]. Such a signalling pathway is supported by an animal model of allergen induced asthma in mice [78].…”
Section: Epigenetic Programming Of Cell Function On the Level Of Tranmentioning
confidence: 75%